ANALISIS FUNDAMENTAL CRYPTOCURRENCY TERHADAP FLUKTUASI HARGA (STUDI KASUS CRYPTOCURRENCY KOIN CARDANO PERIODE 2022-2023) - Chornolius Hendreo; Nia Pratiwi; Syarif Muhammad Ilham (POLITEKNIK LP3I JAKARTA, 2023)
This research aims to analyze Cryptocurrency Fundamentals Against Price Fluctuations (Case Study of Cardano Coin Cryptocurrency for the period 2022 to 2023). This research will analyze the relationship between fundamental factors which include variables such as market capitalization and trading volume with Cardano Coin price fluctuations. This research was conducted at the explanatory level, which aims to explain the causal relationship between the variables involved through hypothesis testing. The method used in this research involves data processing using the SPSS version 26 program. The research results show that the two independent variables, namely Average Trading Volume (X1) and Average Market Capitulation (X2), have a significant influence on Average Price -average (Y) on Cardano cryptocurrency. The high calculated t coefficient values for Average Trading Volume (X1) and Average Market Capulation (X2) indicate that they have a strong influence on Cardano price fluctuations. Average Trading Volume (X1) has a significant positive relationship with Average Price (Y). Average Market Capulation (X2) has a significant negative relationship with Average Price (Y). Keywords : Cryptocurrency, Market Capitalization, Trading Volume, Price Fluctuation, Cardano Coin.